R&D Expenditure and Financial Performance in the Pharmaceutical Industry: A Case Study of Pfizer - Becca, Emma - Lou (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation investigates the impact of R&D expenditure on Pfizer’s financial performance. The study examines the relationship between R&D investment and key financial indicators identified which are revenues and profitability. The analysis reveals a strong and positive correlation between R&D spending and revenue growth which highlights the necessity of sustained investment in innovation in order to protect the competitive edge. On the other hand, the link between R&D and profitability is weaker, which reflects the high costs associated with pharmaceutical R&D. the findings are consistent with industry trends including long development cycles and regulatory compliance impacting short term profitability. The literature review from various industries including banking and aviation highlight the role of strategic investment in improving financial outcomes. Nevertheless, these studies often fail to account for the unique feature of the pharmaceutical industry. This gap emphasizes the need for tailored approaches to evaluating the financial impact of R&D in the pharmaceutical sector. The dissertation recommends several strategies for Pfizer to enhance the financial impact of its R&D expenditures. These include streamlining R&D processes and leveraging advanced technologies such as artificial intelligence .These measures can help Pfizer align its R&D investments with both revenue growth and profitability goals.